Implementasi Framework Laravel dan Model SDLC Waterfall Untuk Pengembangan Sistem Informasi Dokumen Skripsi - Bakhtiar. K; Lemi Iryani; Renny.S (JSAI (Journal Scientific and Applied Informatics), 2024)
Along with the rapid development of information technology, both public and private universities are increasingly competing to develop repository systems in archiving, especially the theses of alumni. This thesis documents that information systems are very necessary to be able to support the progress of a college. With this system, the process of archiving and searching for theses can be done more quickly and accurately. Based on the research problems raised in this study, the prototype of this thesis document information system was built, and after testing the success of the system used using the System Usability Scale (SUS) model with a total value obtained of 87.9, it can be concluded that the system tested shows excellent performance in terms of usability, and provides a satisfying experience for its use.